Neutrality as a Twofold Concept - Zellentin, Alexa (Les ateliers de l'éthique / The Ethics Forum, 2009)
Under the circumstances of pluralism people often claim that the state ought to be neutral towards its citizens’ conceptions of the good life. However, what it means for the state to be neutral is often unclear. This is partly because there are different conceptions of neutrality and partly because what neutrality entails depends largely on the context in which neutrality is demanded. This paper discusses three different conceptions of neutrality – neutrality of impact, neutrality as equality of opportunity and justificatory neutrality – and analyses the strengths and weaknesses of the different conceptions in different contexts. It suggests that there are two common elements of neutrality in all its exemplifications: a) an element of “hands-off” and b) an element of equal treatment. It therefore argues that while justificatory neutrality is necessary for the state to be neutral it is not sufficient and claims that while conceptions of the good must not enter the justification of state regulations, they must be taken into consideration when deliberating the implementation of these regulations.